CONTROL ADECUADO, APLICADO A LA FUNCIÓN DEFICIENTE EN LA UNIDAD EDUCATIVA “CARLOS ALBERTO AGUIRRE AVILÉS” DE LA PARROQUIA LA UNIÓN. - Santana velez, adelaida margarita (2018)
The Carlos Alberto Aguirre Avilés Educational Unit, located in the parish, La Unión - Cantón Babahoyo, was created in 1987, the creators of this work were Mr. Francisco Chávez, Chief of staff of the Clementina estate and Mr. Gastón Rojas, Head of Quality, with the firm desire to serve the children of the workers of the hacienda begins to collect the necessary documentation requested by the Ministry of Education to create the fiscal school that was called Carlos Alberto Aguirre Avilés; putting this name in gratitude to the general manager of the Noboa Corporation, at that time.